2017
DOI: 10.1016/j.mjafi.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of early surgery in infantile esotropia: Our experience in tertiary care hospital

Abstract: m e d i c a l j o u r n a l a r m e d f o r c e s i n d i a 7 3 ( 2 0 1 7 ) 1 2 9 -1 3 Conclusion:The authors recommend surgery before 12 months in all cases of infantile esotropia. The reoperation rates in the current study were considerably low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Im zentraleuropäischen Raum erfolgt eine Augenmuskeloperation meist erst im Vorschulalter. Vorteile für einen frühen Operationszeitpunkt sind sowohl eine höhere Erfolgsrate für die Entwicklung des Binokularsehens [29 -31] als auch eine bessere gesellschaftliche Akzeptanz und eine bessere soziale und psychologische Entwicklung des Kindes [11]. Nachteile eines frühen Operationszeitpunkts sind häufigere Reoperationsraten, eine geringere postoperative Schielwinkelstabilität sowie genauere präoperative Untersuchungsergebnisse bei einem späteren Operationszeitpunkt [1,22,29,32].…”
Section: Dosis-wirkungs-beziehungunclassified
“…Im zentraleuropäischen Raum erfolgt eine Augenmuskeloperation meist erst im Vorschulalter. Vorteile für einen frühen Operationszeitpunkt sind sowohl eine höhere Erfolgsrate für die Entwicklung des Binokularsehens [29 -31] als auch eine bessere gesellschaftliche Akzeptanz und eine bessere soziale und psychologische Entwicklung des Kindes [11]. Nachteile eines frühen Operationszeitpunkts sind häufigere Reoperationsraten, eine geringere postoperative Schielwinkelstabilität sowie genauere präoperative Untersuchungsergebnisse bei einem späteren Operationszeitpunkt [1,22,29,32].…”
Section: Dosis-wirkungs-beziehungunclassified
“…The main treatment of infantile esotropia is extraocular muscle surgery. According to the reported results, 18.3% of patients with infantile exotropia, especially those with more preoperative exotropia, needed a second operation to achieve good alignment 2,3,4,5 . Previous studies have shown that microanisometropia in the astigmatic component 6 may be the cause of infantile esotropia.…”
Section: Introductionmentioning
confidence: 99%